Collaborative pharmaceutical care in an Irish hospital: uncontrolled before-after study. Issue 7 (6th February 2014) - Grimes, Tamasine C; Deasy, Evelyn; Allen, Ann; O'Byrne, John; Delaney, Tim; Barragry, John; Breslin, Niall; Moloney, Eddie; Wall, Catherine
Abstract : Background: We investigated the benefits of the Collaborative P h a rmaceutical C are in T allaght Hospital (PACT) service versus standard ward-based clinical pharmacy in adult inpatients receiving acute medical care, particularly on prevalence of medication error and quality of prescribing. Methods: Uncontrolled before-after study, undertaken in consecutive adult medical inpatients admitted and discharged alive, using at least three medications. Standard care involved clinical pharmacists being ward-based, contributing to medication history taking and prescription review, but not involved at discharge. The innovative PACT intervention involved clinical pharmacists being team-based, leading admission and discharge medication reconciliation and undertaking prescription review. Primary outcome measures were prevalence per patient of medication error and potentially severe error. Secondary measures included quality of prescribing using the Medication Appropriateness Index (MAI) in patients aged ≥65 years. Findings: Some 233 patients (112 PACT, 121 standard) were included. PACT decreased the prevalence of any medication error at discharge (adjusted OR 0.07 (95% CI 0.03 to 0.15)); number needed to treat (NNT) 3 (95% CI 2 to 3) and no PACT patient experienced a potentially severe error (NNT 20, 95% CI 10 to 142). In patients aged ≥65 years (n=108), PACT improved the MAI score from preadmission to discharge (Mann–Whitney U p<0.05; PACT median −1, IQR −3.75 to 0; standard care median +1, IQR −1 to +6). Conclusions: PACT, a collaborative model of pharmaceutical care involving medication reconciliation and review, delivered by clinical pharmacists and physicians, at admission, during inpatient care and at discharge was protective against potentially severe medication errors in acute medical patients and improved the quality of prescribing in older patients.